GE_GERICHTE P/8312/2019 vom 22. Juli 2019 - GE Cour de justice (2019)
DÉFENSE OBLIGATOIRE ; DÉFENSE D'OFFICE ; CONTRAVENTION ; CAS BÉNIN ; ASSISTANCE JUDICIAIRE | cpp.130.letc; cpp.132.letb; cpp.426.al1